REGIONAL AND TRADITIONAL SCENARIO REGARGING THE CONSUMPTION OF THE REGIONAL ROCK OYSTER CRASSOSTREA IRIDESCENS (HANLEY, 1854) IN RESIDENTS AND TOURISTS IN MAZATLAN, SINALOA, MEXICO - Osuna-Muñoz, Román (2023)
The objective of this multidisciplinary interpretive research was to identify the motivations by which the national resident and tourists have a tendency to consume “rock oysters” Crassostrea iridescens (Hanley, 1854) during their daily lives or their stay in the port of Mazatlán, Mexico. The typical Mazatleca cuisine is of great interest, preferably for the consumer and generates a source of economic income for its residents. In Mazatlán, Sinaloa there is the custom of some coastal regional cuisines such as fish ceviche, the consumption of raw shellfish such as the oyster C. iridescens and aguachile (raw shrimp seasoned with lemon, salt, pepper, and serrano chili). An analysis of the sociocultural scenario and the consumer's interest in eating rock oysters was carried out. The relationship between the regional and tourist traditional food was highlighted in these questions: i) if there is a consumption preference between genders (male-female), ii) if the oyster is recognized as a nutritious food, or iii) if there are other sociocultural motivations (i.e. aphrodisiac) and iv) if they are aware of the existing public health risks. 60 surveys were applied, 30 (men) and 30 (women) on the beach when consuming oysters, in the so-called improvised “carretas”, this research was supported by interviews employing key actors such as anglers who sell their products locally. An analysis of consumer eating behavior was carried out, the findings of which provided regional elements where the results show that men and women consume oysters in the same way. With the present work, a multidisciplinary interpretative perspective is obtained on this species of marine mollusk of great commercial value in the port of Mazatlan.